Discursive legitimacy VS. Rational weighing: Contributions to contemporary legal theory by Klaus Günther and Robert Alexy - Moraes, Renato Almeida de; Blanco, Filipe Zanuzzio (Seven Editora, 2024)
This article investigates the theoretical relationship between Klaus Günther and Robert Alexy concerning their conceptions of law. While both philosophers share a foundation in practical rationality and normativity, they diverge significantly in methodological and practical aspects. The objective is to explore the similarities and differences between their theories, emphasizing their contributions to contemporary legal theory. The methodology involves a detailed conceptual analysis through na extensive literature review of their main works, complemented by critical commentary. This study introduces a comparative analysis, examining books such as “The Sense of Appropriateness” by Günther and “A Theory of Legal Argumentation” and “A Theory of Constitutional Rights” by Alexy. The results argue that, although Günther and Alexy both stress the importance of practical rationality and legal normativity, their methodological approaches differ. Günther’s emphasis on democratic participation and discourse provides a more robust framework for legal legitimacy and normativity compared to Alexy’s focus on clear normative structures and proportionality. The conclusions highlight that Günther’s integration of discursive elements and active participation promotes greater justice and equity in the legal system. This approach, enriched by insights from commentators such as Habermas, Fraser, and Forst, is seen as a significant extension of Alexy’s ideas, offering a more inclusive and participatory view of law, which is crucial for contemporary legal theory. DOI:https://doi.org/10.56238/sevened2024.014-012